Assessment of the influence of coal industry on the environment - Novytskyi I.Yu.; Perov M.O.; Makortetskiy M.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
Coal is at present and will remain in future the main type of energy resources for thermal and electric generation in Ukraine. This is caused by its reserves, which probably will be sufficient for several centuries, the shortage of natural gas, and insignificant part of renewable energy sources in the country energy balance. In addition, so far the product of coal processing – coke is the indispensable raw material for ferrous metallurgy.At the same time, the coal industry is a powerful source of harmful action on the environment. This influence extends to all its spheres: atmosphere (including the ozone layer), hydrosphere (water basins and underground water), lithosphere, and earth's surface.Ukraine’s commitments in the context of deepening integration processes with West-European countries, including environmental protection in spite of enhancing the role of coal as the main energy carrier for domestic power engineering, will inevitably be accompanied by the introduction of more stringent ecological requirements for the operation of enterprises that mine, process, and consume coal. Therefore, investigations of the influence of activities of coal-industry enterprises on the environment with the aim of ensuring the ecological safety of Ukraine are relevant.The present article is devoted to the assessment of influence of the main contaminants formed in the course of activity of the coal-industry enterprises. We analyze the sources of contamination according to different classification groups and give their quantitative characteristics.Emphasis is placed on the necessity to introduce at the regional level a set of scientific and engineering measures that will stabilize the ecological situation in the territories of Donetsk, Luhansk, and Dnipropetrovsk regions as well as the Lviv-Volyn basin.